2015
DOI: 10.1093/mnras/stv1869
|View full text |Cite
|
Sign up to set email alerts
|

Deep radio imaging of 47 Tuc identifies the peculiar X-ray source X9 as a new black hole candidate

Abstract: We report the detection of steady radio emission from the known X-ray source X9 in the globular cluster 47 Tuc. With a double-peaked C IV emission line in its ultraviolet spectrum providing a clear signature of accretion, this source had been previously classified as a cataclysmic variable. In deep ATCA imaging from 2010 and 2013, we identified a steady radio source at both 5.5 and 9.0 GHz, with a radio spectral index (defined as S ν ∝ ν α ) of α = −0.4 ± 0.4. Our measured flux density of 42 ± 4 µJy beam −1 at… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
85
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 131 publications
(87 citation statements)
references
References 147 publications
(239 reference statements)
2
85
0
Order By: Relevance
“…Thanks to the increased sensitivity of new Karl G. Jansky Very Large Array (VLA) and ATCA receivers, faint radio sources have been detected in a number of GCs (e.g. Strader et al 2012;Chomiuk et al 2013;Miller-Jones et al 2015). There are several possibilities for these sources.…”
Section: Radio Sources In Globular Clustersmentioning
confidence: 99%
See 1 more Smart Citation
“…Thanks to the increased sensitivity of new Karl G. Jansky Very Large Array (VLA) and ATCA receivers, faint radio sources have been detected in a number of GCs (e.g. Strader et al 2012;Chomiuk et al 2013;Miller-Jones et al 2015). There are several possibilities for these sources.…”
Section: Radio Sources In Globular Clustersmentioning
confidence: 99%
“…The dashed grey line shows the L R -L X correlation for black holes from Gallo et al (2014). The larger purple circles are radio-selected black hole candidates (Strader et al 2012;Chomiuk et al 2013;Miller-Jones et al 2015;Tetarenko et al 2016;Bahramian et al 2017;Shishkovsky et al 2018). The light-green triangles mark known transitional millisecond pulsars (Hill et al 2011;Papitto et al 2013;Deller et al 2015;Bogdanov et al 2018).…”
Section: U18: a Hidden Msp?mentioning
confidence: 99%
“…In addition, as some early works on advectiondominated accretion flows (Narayan & Yi 1994) predict that the emission from the hot inner flow can start to fall out of the X-ray band at very low Eddington fraction, it is possible that most of the emission in VLA J2130+12 is at far-UV rather than X-ray frequencies, implying that the observed high radio/ X-ray flux ratio could be explained in this case without invoking an enormous beaming factor. The large radio luminosity may also indicate a higher than average stellar- Gallo et al 2012Gallo et al , 2014Ratti et al 2012;Corbel et al 2013;Munar-Adrover et al 2014;Dzib et al 2015), and the yellow circles represent the BHCs in M22, M62, and 47 Tuc (Strader et al 2012b;Chomiuk et al 2013;Miller-Jones et al 2015). The blue circles represent NS systems in the hard state (Rutledge et al 1998;Moore et al 2000;Migliari et al 2003Migliari et al , 2010Migliari et al , 2011Migliari & Fender 2006;Tudose et al 2009;Miller-Jones et al 2010;Tetarenko et al 2016a).…”
Section: Optical Analysismentioning
confidence: 99%
“…The remaining four are found in globular clusters (GCs; Strader et al 2012b;Chomiuk et al 2013;Miller-Jones et al 2015). The vast majority of these Galactic BHXBs are low-mass X-ray binaries (LMXBs) where mass transfer occurs via Roche lobe overflow of a secondary companion with a mass of M 2  3 M e and spectral type A or later.…”
Section: Introductionmentioning
confidence: 99%
“…Kremer et al 2019), so it is not surprising studies are starting to find them, even if their signatures are challenging to observe. Currently there are a handful of accreting black hole candidates in Milky Way globular clusters (Strader et al 2012;Chomiuk et al 2013;Miller-Jones et al 2015;Shishkovsky et al 2018), and there is one dynamically-confirmed black hole candidate in which there is no evidence for accretion (Giesers et al 2018). There are a handful of other black hole candidates in extragalactic globular clusters, including globular clusters in NGC 1399, NGC 4472 and NGC 4649 (Shih et al 2010;Irwin et al 2010;Maccarone et al 2011;Roberts et al 2012;Dage et al 2019).…”
Section: Introductionmentioning
confidence: 99%